CURRENT STATUS OF STUDENTS' PHYSICAL ACTIVITY IN TAY BAC UNIVERSITY AND SOME FACTORS RELATED SCHOOL YEAR 2020 – 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: Describe the reality of physical activity and personal factors and family related to physicalactivity of Tay Bac University students in the school year 2020-2021.Methods: A cross-sectional descriptive study with analysis was conducted on 832 students at TayBac university.Research results: The rate of adequate physical activity was 54,4%, the rate of lack of physicalactivity was 45,6%. In which, 24,6% of students have active physical activity, 29,8% have moderatephysical activity and 45,6% have low physical activity. The rate of lack of physical activity in women(50,5% of the total number of women) is higher than men (38,1% of the total number of men). Thecorrelation analysis showed that there are factors such as gender (p
Keywords: Physical activity, Metabolic Equivalents Task unit, students, Tay Bac University.